microRNA as Potential Biomarker for Pediatric Tuberculosis? (Indian Journal of Forensic Medicine & Toxicology, 2020)
The diagnosis of pediatric TB is based on history taking, clinical symptoms, physical examination and support. In recent years the role of microRNA (miRNA or miR) has become a concern for researchers as biomarkers of diagnosis and therapy in TB in adults and children. MicroRNA is a ribonucleic acid that does not encode proteins with 18-25 nucleotide transcripts that interact with gene targets and regulate mRNA expression. miRNA works with other regulatory elements such as transcription factors to control mRNA translation. More than 100 different miRNAs are expressed by immune system cells; they have the potential to broadly influence the molecular pathways that control the development and function of innate and adaptive immune response regulation. During TB infection, the innate immune response provides an initial defense mechanism against infection. It is well known that macrophages are the main stem cells for mycobacteria, survival in macrophages is determined by host-pathogen interactions. Several studies have shown that miRNA can be used as a biomarker and TB therapy agent because it is stable in plasma and other body fluids, difficult to degrade and excreted in the form of exosomes or micro vesicles. Other studies say miRNA is stable despite repeated exposure to heat, cold, acids, bases, and other extreme conditions. microRNA levels are reported to be increased in individuals with TB.